Cardiac arrhythmia and hypoglycaemia in patients receiving haemodialysis with and without diabetes (the CADDY study): protocol for a Danish multicentre cohort study - Jesper Hastrup Svendsen; Theis Lange; Kirsten Nørgaard; Morten Lindhardt; Mads Hornum; Bo Feldt-Rasmussen; Marianne Rix; Søren Zöga Diederichsen; Dea Haagensen Kofod; Tobias Bomholt; Mads Ørbæk Andersen; Ylian Liem; et al. (BMJ Open, 2023)
Introduction Patients receiving haemodialysis are at increased risk of arrhythmias and sudden cardiac death, but data on arrhythmia burden and the pathophysiology remain limited. Among potential risk factors, hypoglycaemia is proposed as a possible trigger of lethal arrhythmias. The development of implantable loop recorders (ILR) and continuous glucose monitoring (CGM) enables long-term continuous ECG and glycaemic monitoring. The current article presents the protocol of a study aiming to increase the understanding of arrhythmias and risk factors in patients receiving haemodialysis. The findings will provide a detailed exploration of the burden and nature of arrhythmias in these patients including the potential association between hypoglycaemia and arrhythmias.Methods and analysis The study is an investigator-initiated, prospective, multicentre cohort study recruiting 70 patients receiving haemodialysis: 35 with diabetes and 35 without diabetes. Participants are monitored with ILRs and CGM for 18 months follow-up. Data collection further includes a monthly collection of predialysis blood samples and dialysis parameters. The primary outcome is the presence of clinically significant arrhythmias defined as a composite of bradycardia, ventricular tachycardia, or ventricular fibrillation. Secondary outcomes include the characterisation of clinically significant arrhythmias and other arrhythmias, glycaemic characteristics, and mortality. The data analyses include an assessment of the association between arrhythmias and hypoglycaemia and hyperglycaemia, baseline clinical variables, and parameters related to kidney failure and the haemodialysis procedure.Ethics and dissemination The study has been approved by the Ethics Committee of the Capital Region of Denmark (H-20069767). The findings will be presented at national and international congresses as well as in international peer-reviewed scientific journals.Trial registration number NCT04841304.